Programa de interpretación ambiental para el turismo en la Reserva Nacional Allpahuayo Mishana, Loreto, Perú - Soria Solano, Benjamin (2022)
Although the Allpahuayo Mishana National Reserve (RNAM) was created in 2004, it still does not have an Environmental Interpretation Program (PIA), a basic tool for the indirect physical protection of the tourist resources and the natural and cultural heritage of the RNAM. The objective of this research is to develop a PIA for tourism in the RNAM, based on, the inventory of interpretative resources tourist, supported by the infrastructure sub programs, community projection and requirements for the execution of the PIA. The research has a qualitative-descriptive approach, of the action-research type, based on the analysis, evaluation and interpretation of documentary information on the subject, which aims to change and improve the environmental interpretation, both in the RNAM and the regional context. The most important part of this research is the discovery of vegetal species and communities (different from other territorial sites in the region), human communities (villages or communities) selected for the interpretation, both in situ (interpretative trails) and ex situ (interpretation center), as the case may be, of tourist resources of the natural and cultural heritage, according to their Interpretative Potential Index (IPI), as a result of a field work in both tourist areas of the RNAM, basic elements of a PIA. The proposal to improve interpretive services is also presented.